Between life and death: the brain twilight zones - Charpier, Stéphane (Frontiers in Neuroscience, 2023)
Clinically, and legally, death is considered a well-defined state of the organism characterized, at least, by a complete and irreversible cessation of brain activities and functions. According to this pragmatic approach, the moment of death is implicitly represented by a discrete event from which all cerebral processes abruptly cease. However, a growing body of experimental and clinical evidence has demonstrated that cardiorespiratory failure, the leading cause of death, causes complex time-dependent changes in neuronal activity that can lead to death but also be reversed with successful resuscitation. This review synthesizes our current knowledge of the succeeding alterations in brain activities that accompany the dying and resuscitation processes. The anoxia-dependent brain defects that usher in a process of potential death successively include: 1) a set of changes in electroencephalographic (EEG) and neuronal activities, 2) a cessation of brain spontaneous electrical activity (isoelectric state), 3) a loss of consciousness whose timing in relation to EEG changes remains unclear, 4) an increase in brain resistivity, caused by neuronal swelling, concomitant with the occurrence of an EEG deviation reflecting the neuronal anoxic insult (the so-called "wave of death", or "terminal spreading depolarization"), followed by, 5) a terminal isoelectric brain state leading to death. However, a timely restoration of brain oxygen supply – or cerebral blood flow – can initiate a mirrored sequence of events: a repolarization of neurons followed by a re-emergence of neuronal, synaptic, and EEG activities from the electrocerebral silence. Accordingly, a recent study has revealed a new death-related brain wave: the " wave of resuscitation ", which is a marker of the collective recovery of electrical properties of neurons at the beginning of the brain's reoxygenation phase. The slow process of dying still represents a terra incognita, during which neurons and neural networks evolve in uncertain states that remain to be fully understood. As current event-based models of death have become neurophysiologically inadequate, I propose a new mixed (event-process) model of death and resuscitation, incorporating cerebral twilight zones (with still unknown neuronal and synaptic processes) punctuated by two characteristic cortical waves providing real-time biomarkers of death- and resuscitation.